2018
DOI: 10.2519/jospt.2018.7811
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Screening for Prediction of Referral and Outcome (OSPRO) for Musculoskeletal Pain Conditions: Results From the Validation Cohort

Abstract: Study Design Observational, prospective cohort Background Musculoskeletal pain is a common reason to seek healthcare and earlier non-pharmacological treatment and enhancement of personalized care options are two high priority areas. Validating concise assessment tools is an important step in establishing better care pathways. Objectives To determine the predictive validity of Optimal Screening for Prediction of Referral and Outcome (OSPRO) tools for individuals with neck, low back, shoulder, or knee pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…Using this method, OSPRO-YF scores predicted 12-month pain severity, disability, and health care utilization outcomes following physical therapy. 5,23,40 However, to date additional psychometric properties of the OSPRO-YF have not been further investigated. A better understanding of the underlying constructs measured by the tool is necessary even though the tool was developed with an established theoretical structure.…”
mentioning
confidence: 99%
“…Using this method, OSPRO-YF scores predicted 12-month pain severity, disability, and health care utilization outcomes following physical therapy. 5,23,40 However, to date additional psychometric properties of the OSPRO-YF have not been further investigated. A better understanding of the underlying constructs measured by the tool is necessary even though the tool was developed with an established theoretical structure.…”
mentioning
confidence: 99%
“…The predictive validity of the OSPRO‐YF has been established with a separate cohort of patients with neck ( n = 98), shoulder ( n = 107), low back ( n = 118), or knee ( n = 82) conditions (George et al, ). The results demonstrated that the OSPRO‐YF at baseline and at 4 weeks was a statistically significant predictor of 12‐month pain intensity, disability, and quality of life.…”
Section: Multidimensional Psychosocial Screening Toolsmentioning
confidence: 99%
“…The results demonstrated that the OSPRO‐YF at baseline and at 4 weeks was a statistically significant predictor of 12‐month pain intensity, disability, and quality of life. However, the amount of variance explained by the OSPRO‐YF was small ( R 2 = 0.04–0.07) (George et al, ).…”
Section: Multidimensional Psychosocial Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beliefs, attitudes, fears and emotional responses are omnipresent across all types of LBP presentations, and these can be measured with validated assessment tools (eg, Start Back Screening Tool, Orebro Musculoskeletal Pain Questionnaire, or Optimal Screening for Prediction of Referral and Outcome tool) 7. Systematically using these tools provides the clinician an opportunity to further explore psychosocial factors in clinical practice.…”
Section: Call To Actionmentioning
confidence: 99%